Assessing and Managing Rapid Credit Growth and the Role of Supervisory and Prudential Policies - Pazarbasioglu, Ceyla (IMF Working Papers; Working Paper, 2005)
This paper reviews trends in bank lending to the private sector, with a particular focus on Central and Eastern European countries, and finds that rapid growth of private sector credit continues to be a key challenge for most of these countries. The paper discusses possible implications for economic and financial stability and the policy options available to counter and reduce these risks. It argues that the authorities will need to focus on the implications for both the macro economy and the financial system and, depending on their assessment, may need a comprehensive policy response comprising a mix of macro and prudential policies. In particular where there are limitations to the effective use of monetary and fiscal measures, supervisory and prudential policy responses will have a key role in addressing financial stability concerns.